Trastuzumab emtansine for patients with non–small cell lung cancer positive for human epidermal growth factor receptor 2 exon-20 insertion mutations. (February 2022) - Iwama, Eiji; Zenke, Yoshitaka; Sugawara, Shunichi; Daga, Haruko; Morise, Masahiro; Yanagitani, Noriko; Sakamoto, Tomohiro; Murakami, Haruyasu; Kishimoto, Junji; Matsumoto, Shingo; Nakanishi, Yoichi; Goto, Koichi; et al.
Abstract: Background: Human epidermal growth factor receptor 2 (HER2) mutations are present in ∼3% of patients with non–small cell lung cancer (NSCLC), with exon-20 insertions accounting for ∼90% of such HER2 mutations and having been identified as driver oncogenic alterations. Antibody–cytotoxic drug conjugates including trastuzumab deruxtecan have shown an excellent efficacy for NSCLC with HER2 mutations. We have now performed a phase II study to evaluate the efficacy of ado-trastuzumab emtansine (T-DM1) for NSCLC positive for HER2 exon-20 insertion mutations. Patients and methods: Eligible patients with HER2 exon-20 insertion mutations confirmed by next-generation sequencing or multiplex polymerase chain reaction platforms and a history of one or two lines of chemotherapy received T-DM1 (3.6 mg/kg) intravenously every 21 days. The primary end-point of the study was the objective response rate (ORR). Results: Between February 2019 and July 2020, 22 patients were enrolled in the study. A775_G776insYVMA was the most frequent HER2 exon-20 insertion mutation, accounting for 19 (86.4%) of the 22 patients. The ORR was 38.1% (90% confidence interval, 23.0–55.9%), and the disease control rate was 52.4%. The median duration of response was 3.5 months, and the median progression-free survival and median overall survival were 2.8 and 8.1 months, respectively. Toxicity was mild, with the frequency of adverse events of grade ≥3 being low. Conclusion: T-DM1 is a potential treatment option for patients with NSCLC with HER2 exon-20 insertion mutations. Further investigation of biomarkers for T-DM1 is warranted to improve its efficacy for NSCLC with such mutations. Clinical trial number: JapicCTI-194620 Highlights: Ado-trastuzumab emtansine was tested for patients with non-small cell lung cancer. The objective response rate for T-DM1 in these patients was 38.1%. Toxicity was mild, with the frequency of adverse events of grade ≥3 being low.